Optical coherence tomography angiography of the foveal avascular zone in retinal vein occlusion - Wons, Juliana; Pfau, Maximilian; Wirth, Magdalena A.; Freiberg, Florentina Joyce; Becker, Matthias D.; Michels, Stephan (Ophthalmologica, 2016)
Purpose: The aim of the study was to visualize and to quantify pathological foveal avascular zone (FAZ) alterations through optical coherence tomography angiography (OCT-A) in eyes with retinal vein occlusion (RVO) in comparison to the unaffected fellow eyes. Procedures: OCT-A was conducted with the Avanti® RTVue 100 XR system (Optovue Inc., Fremont, Calif., USA). The borders of the superficial vascular layer (SVL) were defined as 3 μm below the internal limiting membrane and 15 μm below the inner plexiform layer, and for the deep vascular layer (DVL) as 15 and 70 μm below the inner plexiform layer, respectively. The length of the horizontal, vertical and maximum FAZ was manually measured for the SVL and DVL in each eye. Additionally, the angle between the maximum FAZ diameter and the papillomacular plane was measured. Results:OCT-A depicted defects within the perifoveal vasculature in eyes with branch retinal vein occlusion (BRVO; n = 11) and central retinal vein occlusion (CRVO; n = 8). These resulted in an enlargement of the maximum FAZ diameter in eyes with RVO (n = 19) in comparison to the healthy fellow eyes (n = 19; 921 ± 213 vs. 724 ± 145 µm; p = 0.008). Furthermore, a significant correlation was found between best-corrected visual acuity (BCVA) and the maximum FAZ diameter in the DVL (Spearman's ρ = -0.423, p < 0.01). Lastly, in the eyes with RVO, the angle between the papillomacular plane and the maximum FAZ diameter was only in 21.05% (SVL) and 15.79% (DVL) of the cases at 0 ± 15 or 90 ± 15°, respectively. In healthy eyes, these angles (which putatively represent a regular FAZ configuration) were more prevalent (SVL 68.42 vs. 21.05%, p = 0.003; DVL 73.68 vs. 15.79%, p < 0.001). Conclusion: OCT-A shows morphological alterations of the FAZ in eyes with CRVO and BRVO. The correlation of the maximum FAZ diameter with BCVA suggests that these alterations are functionally relevant.
Gesehen am 25.02.2021